Low Electron Temperatures Observed at Mars by MAVEN on Dayside Crustal Magnetic Field Lines. Issue 9 (5th September 2019) - Sakai, Shotaro; Cravens, Thomas E.; Andersson, Laila; Fowler, Christopher M.; Mitchell, David L.; Mazelle, Christian; Thiemann, Edward M. B.; Eparvier, Francis G.; Brain, David A.; Seki, Kanako
Abstract: The ionospheric electron temperature is important for determining the neutral/photochemical escape rate from the Martian atmosphere via the dissociative recombination of O2 + . The Langmuir Probe and Waves instrument onboard MAVEN (Mars Atmosphere and Volatile EvolutioN) measures electron temperatures in the ionosphere. The current paper studies electron temperatures in the dayside for two regions where (1) crustal magnetic fields are dominant and (2) draped magnetic fields are dominant. Overall, the electron temperature is lower in the crustal‐field regions, namely, the strong magnetic field region, which is due to a transport of cold electrons along magnetic field lines from the lower to upper atmosphere. The electron temperature is also greater for high solar extreme ultraviolet conditions, which is associated with the local extreme ultraviolet energy deposition. The current models underestimate the electron temperature above 250‐km altitude in the crustal‐field region. Electron heat conduction associated with a photoelectron transport in the crustal‐field regions is altered due to kinetic effects, such the magnetic mirror and/or ambipolar electric field because the electron mean free path exceeds the relevant length scale for electron temperature. The mirror force can affect the electron and heat transport between low altitudes, where the neutral density and related electron cooling rates are the greatest, and high altitudes, while the ambipolar electric field decelerates the electron's upward motion. These effects have not been included in current models of the electron energetics, and consideration of such effects on the electron temperature in the crustal‐field region should be considered for future numerical simulations. Key Points: At high altitudes, the electron temperature is lower for the crustal‐field region than for the IMF‐dominated draped regions The low temperatures for the crustal‐field region are due to a heat transport along the field lines between lower and upper atmosphere Kinetic effects such the magnetic mirror and the ambipolar electric field may affect the heat transport along crustal magnetic field lines